2019
DOI: 10.1590/rbz4820180273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic Lactobacillus reuteri XC1 coexpressing endoglucanase and phytase on intestinal pH and morphology, carcass characteristics, meat quality, and serum biochemical indexes of broiler chickens

Abstract: This study investigated the effect of transformed Lactobacillys reuteri on intestinal pH and morphology, carcass characteristics, meat quality, and serum biochemical indexes of broiler chickens. A total of 480 broilers were assigned to six treatment groups and fed a phosphorus-adequate diet, a phosphorus-deficient diet, or a phosphorus-deficient diet containing different L. reuteri recombinants. The results showed that transformed L. reuteri decreased the pH in the duodenum and jejunum of chickens at day 21, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…The decreasing of shear force in this study indicated an improvement in intramuscular quality after LAB supplementation. Another study also showed a decrease in the shear-force of 42-dayold broiler meat after administration of Lactobacillus strain in the diet, with a lower value than the results of this study, which was 29.6-42.9N (Wang et al 2019). Moreover, FFA is one of the most common chemical parameters used to determine the quality of a product (Ozkececi et al 2008).…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…The decreasing of shear force in this study indicated an improvement in intramuscular quality after LAB supplementation. Another study also showed a decrease in the shear-force of 42-dayold broiler meat after administration of Lactobacillus strain in the diet, with a lower value than the results of this study, which was 29.6-42.9N (Wang et al 2019). Moreover, FFA is one of the most common chemical parameters used to determine the quality of a product (Ozkececi et al 2008).…”
Section: Discussioncontrasting
confidence: 40%
“…The ability to absorb feed nutrients is largely determined by the histomorphological indicators of the small intestine, especially the size of the villus, where the increase the villus height will enlarge the surface area of the small intestine, so that the ability to absorb the available nutrients in the intestinal lumen is greater (Chichlowski et al 2007). Some investigations demonstrated that the height of jejunal and ileal villi in chicken was increasing after supplementation with Lactobacillus group (Forte et al 2018;Wang et al 2019). Our previous observation also revealed that there was an increase in the weight and length of the small intestine after LAB supplementation (Yosi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them showed that prebiotics and probiotics do not affect meat quality. For example, addition of a probiotic Lactobacillus reuteri (2.5×10 8 cfu/mL) to broiler chicken diet over the 42 days of the experiment did not affect meat quality [ 23 ]. Another study with inclusion of probiotic S. cerevisiae 1 g/kg of diet and prebiotic MOS 1 g per kg of diet into turkey diet for 10 weeks also showed that these feed additives do not influence the different parameters of meat quality, including the amount of protein [ 24 ].…”
Section: Discussionmentioning
confidence: 99%